Produção de leite em sistema Compost Barn no noroeste do estado do Rio Grande do Sul - Dalberto, Genuina (2018)
Within the scope of milk production one of the most recent innovations is the Compost Barn (CB) confinement system, which has been gradually deployed in producing regions in the state of Rio Grande do Sul (RS). The general objective of this research was to analyze milk production in the Compost Barn system in the Northwest of the state of Rio Grande do Sul. The first stage of the research consisted of a bibliographical review, the discussion about CB system was marked by bibliometric analysis in second, for the analysis of primary data, technical, socioeconomic and decision-making indicators were used as parameters in the literature. The subjects of the research are 15 milk producers who implanted the CB system in the Northwest region of RS, associated with the Co-op COTRIJAL. The data were collected between November 2017 and February 2018, through a structured script, applied in agricultural production units (UPAs). Regarding bibliometric analysis, it was identified that, although the CB system was implanted 18 years ago in the USA, the international literature shows that the studies carried out and/or the publication of these can be considered reduced (75 documents in total) and are concentrated in the USA. The performance of the herd in relation to the milk quality was heterogeneous in the UPAs analyzed, the average data for the housed animals showed that the majority (53.33%) of the UPAs, besides the high productivity (≥ 30 L/cow/d) had mean CCS of the tank (360 x 1000 cells/mL) as recommended by the IN 31. From a comparative analysis, three UPAs were identified and grouped in which the focus is the exclusively milk activity (SP1). In terms of technical performance, these UPAs, considering the analyzed period, have obtained results that approximate UPAs of reference countries in milk production with high levels of quality. Regarding economic performance, although there is scope for further improvement of the indicators, they are in a condition of progressive capitalization, since they provide adequate remuneration for land and family labor. The second group is composed by the grouping of 12 UPAs in which the milk activity is performed in combination with the production of grains for commercial purposes (SP2), in this, two contrasting situations are observed. On the one hand, the UPAs can be considered efficient and in the phase of capitalization, they present a significant productivity performance of the land and family labor, although in average, to a lower intensity than the UPAs of SP1; on the other, three UPAs are identified in which the performance of the milk activity can be considered unsatisfactory and the production factors are remunerated in their fullness; considering milk production, there is a low milk yield (19.66 L/cow/d), since all UPAs that present a positive Agricultural Income had an average productivity of 28 liters or more. Other factors such as schooling, planning and knowledge about the Compost Barn System tend to contribute to explain the heterogeneity found in this set of UPAs.